Analisis Nilai Perusahaan Sebelum Dan Sesudah Melakukan Right Issue - Salsabila Safiratunnajah; Nor Norisanti; R. Deni Muhammad Danial (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study is to analyze, describe, and measure the difference in the value of the company before and after the rights issue. The object of this research is the value of the company which is proxied by EPS, PER, PBV, and the Tobin's Q ratio before and after conducting a rights issue on companies listed on the BEI. The research method used is quantitative with a descriptive comparative approach, which is a method that looks at the general description of the calculation results of the variables and the differences between the variables before and after the rights issue. Data analysis techniques start from data compilation, data tabulation to testing. The test uses the data normality test, and the different test uses SPSS with the data requirements. Based on the results of the study, it was found that the calculation results increased and decreased each period, the EPS ratio showed no significant difference between the companies before and after the rights issue, in contrast to the PER, PBV, and Tobin's Q ratios which showed differences in the companies before and after do a rights issue. Keywords: Company Value, Tobin;s Q, Right Issue.